Pengaruh Brand Awareness, Keunggulan Produk Dan Kepercayaan Terhadap Minat Nasabah Menabung Di Bank Nagari Cabang Lubuk Buaya Padang - Elsa Yuli Ratna Sari; Lidya Martha (Jurnal Mirai Management, 2023)
The purpose of this study was to test brand awareness, product superiority and trust in customers' interest in saving at Bank Nagari Branch Lubuk Buaya, Padang. This type of research is quantitative research. This research was conducted at Bank Nagari Branch Lubuk Buaya, Padang. The sampling method used the accidental sampling method with the slovin formula of 98 respondents. Data analysis techniques used were validity, reliability, descriptive analysis, normality test, multicollinearity test, heteroscedasticity test, multiple regression analysis, and t test. The results showed that brand awareness, product superiority and trust had a positive and significant effect on the customer's saving intention at Bank Nagari Branch Lubuk Buaya,Padang. Keywords: brand awareness, product excellence, trust and customer interest in saving.